SWOT analysis of wine tourism development opportunities in the Trstenik vineyard district - Stojković, Jelena; Milićević, Snežana (Hotel and Tourism Management, 2020)
Serbia is traditionally a wine-growing region and it is slowly approaching those countries that have benefited from the development of this type of tourism. The subject of this paper is the analysis of the Trstenik vineyard district, whose wine-growing areas, although within a small municipality in Central Serbia, are one of the largest in the country within the Three Morava Rivers region. The Trstenik vineyard district can take a chance and find its place in this specific tourism market. The aim of the paper is to present all the strengths and opportunities, but also the threats and weaknesses for the development of wine tourism in this wine district. This is presented through SWOT analysis. All the results could be used to make this municipality as wine tourism destination in Serbia.